Creative self-efficacy and its factors: An empirical study of information system analysts and programmers. - Yang, Heng-Li; Cheng, Hsiu-Hua (Computers in Human Behavior, 2009)
Based on a survey of 94 information systems developers, this study explored how personal factors (i.e. computer self-efficacy and domain-specific information technology skills), contextual factors (i.e. strength of ties and degree centrality) and creative self-efficacy are related. Regression analysis results demonstrate that system analysts and programmers differ in terms of influencing factors on creative self-efficacy. Domain-specific skills were the main influence in the system analyst model, followed by degree centrality. In comparison, degree centrality was the only influence in the programmer model. Degree centrality exerted a negative influence in both groups. Additionally, among system analysts, the strength of ties slightly influenced creative self-efficacy, while computer self-efficiency and domain-specific information technology skills exerted only small influences on programmers. Copyright (c) 2009 Elsevier Ltd.